Morpho-agronomic diversity of local ABB banana ‘Roid’ in Jatigede, West Java - Ade Ismail; Fajar Maulana Wijaya Kusumah; Safira Damayanti Rudianto; Agung Karuniawan; Citra Bakti; Anne Nurbaity (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2025)
Bananas are one of Indonesia’s most important horticultural crops, valued for their adaptability and economic potential. Among them, the Roid banana (ABB) (Musa spp.) stands out as a local variety native to West Java-Indonesia, particularly the Jatigede District, Sumedang Regency where it thrives naturally without agronomic inputs. Known for its resistance to pests and diseases, long shelf life, and strong fruit attachment that reduces post-harvest losses, the Roid banana remains underutilized and understudied. Despite its advantages, research on its genetic diversity is limited, highlighting the need for characterization as a foundation for conservation and breeding. This study, conducted from October to December 2023 in the Jatigede District, aimed to analyze the distribution patterns and genetic diversity of Roid bananas. Characterization used a survey method and purposive sampling in situ. Results revealed two primary clusters dominated by accessions from Ciranggem and Jemah Villages. Key traits supported clusters were peduncle curvature, bunch length and density, number of fruit hands, male flower attitude, apex shape, skin color, plant height, and the presence of hermaphrodite flowers. The genetic diversity based on Euclidean distances was 0.47 to 11.92. The Index of Cultural Significance value was 105, implying a very high level of utilization diversity. These findings highlight the genetic richness and cultural importance of Roid bananas, offering valuable insights for future conservation and breeding programs. Keywords: characterization; cluster analysis; exploration; Index Cultural Significance (ICS); Musa spp.